PENGARUH TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN LABA PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ismanto, Erwinargo (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This research using the Kruskal-Wallis test to test the presence or absence of the influence of bank soundness to profit growth. This study uses two variables, namely the health of banks and profit growth. Bank soundness variables refer to the provisions of Bank Indonesia through Bank Indonesia Circular Letter No. 6/23/DPNP May 31, 2004 on the evaluation of the bank based on the CAMEL aspect Capital (CAR), Asset (APB and PPAP), Management (ROA), Earning (ROA) and Liquidity (LDR) and then the bank can be classified according to the criteria of the bank. Meanwhile, earnings growth variables using the model to determine Î”NII repricing of the sample banks. The results using the Kruskal-Wallis test showed that the effect on the health of banks profit growth.